PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI SEKTOR PERTAMBANGAN PROVINSI KALIMANTAN TIMUR (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The aim of this study was to determine the effect of the Mining Sector Investment and Employment Mining Sector in East Kalimantan province. Methods or analysis tools used in this study is multiple regression analysis approach classical assumptions are processed in a detailed explanation. This study used secondary data obtained from the Central Statistics Agency (BPS). From the results of data analysis that I do can be concluded that: (1) As a region that relies heavily on investment, economic growth in the province of East Kalimantan is still affected by the performance of mining production. (2) Lack of Labor could cause an obstacle to mining production.Keywords: Multiple Regression Analysis, Investment, Economic Growth, Employment.